Global Epidemiology and Antimicrobial Resistance of Metallo-β-Lactamase (MBL)-Producing Acinetobacter Clinical Isolates: A Systematic Review - Matthew E. Falagas; Dimitrios S. Kontogiannis; Maria Zidrou; Charalampos Filippou; Giannoula S. Tansarli (Pathogens)
This systematic review assessed the global epidemiology of metallo-β-lactamase (MBL)-producing Acinetobacter clinical isolates and the associated antimicrobial resistance. A total of 475 relevant articles from the Cochrane Library, Google Scholar, PubMed, Scopus, and Web of Science were identified and screened as potentially eligible articles. Data from 85 articles were extracted for the analysis. Most reports on MBL-producing Acinetobacter clinical isolates originated from Asia [68/85 (80%) studies] and Africa [14/85 (16.5%) studies]. There were also scarce reports from Europe and America. The blaVIM (in 31 studies), blaIMP (in 29 studies), and blaNDM (in 21 studies) genes were the most commonly identified genes. In 22 out of 28 (78.6%) studies with comparable data, the proportions of MBL-producing pathogens detected using phenotypic methods were numerically higher than those using genotypic methods. MBL-producing Acinetobacter isolates showed high resistance (up to 100%) to several antibiotic classes, including carbapenems, cephalosporins, fluoroquinolones, and monobactams. However, they showed low resistance to colistin [ranging from 0% (in six studies) to 14.3% (in one study)] and to tigecycline [0% (in three studies)]. No risk of bias assessment was conducted. The findings emphasize the global spread of MBL-producing Acinetobacter and the need for enhanced antimicrobial stewardship, infection control measures, and surveillance.